Pemahaman Nazhir Tentang Wakaf Produktif dan Faktor-Faktor Penentunya - Mochammad Zainun Nafi'uddin; Marlina Ekawaty (Badan Wakaf Indonesia, 2019)
The purpose of this study was to determine Nazhir's understanding of productive waqf and its influencing factors. The subjects in this study were Nazhir in Malang City. The method used in this study is to use logistic regression analysis. The results obtained from this study indicate that 78% of Nazhir understands productive waqf. Meanwhile, the factors that significantly influence Nazhir's understanding of productive waqf include income, productive waqf training, and readiness to manage productive waqf. Keywords: Productive Waqf, Nazhir, Understanding Productive Waqf.